Modulating hydrogen adsorption via charge transfer at the semiconductor–metal heterointerface for highly efficient hydrogen evolution catalysis - Liu, Yuhang (2023)
Designing and synthesizing highly efficient and stable electrocatalysts for hydrogen evolution reaction (HER) is important for realizing the hydrogen economy. Tuning the electronic structure of the electrocatalysts is essential to achieve optimal HER activity, and interfacial engineering is an effective strategy to induce electron transfer in a heterostructure interface to optimize HER kinetics. In this study, ultrafine RhP2 /Rh nanoparticles are synthesized with a well-defined semiconductor-metal heterointerface embedded in N,P co-doped graphene (RhP2 /Rh@NPG) via a one-step pyrolysis. RhP2 /Rh@NPG exhibits outstanding HER performances under all pH conditions. Electrochemical characterization and first principles density functional theory calculations reveal that the RhP2 /Rh heterointerface induces electron transfer from metallic Rh to semiconductive RhP2 , which increases the electron density on the Rh atoms in RhP2 and weakens the hydrogen adsorption on RhP2 , thereby accelerating the HER kinetics. Moreover, the interfacial electron transfer activates the dual-site synergistic effect of Rh and P of RhP2 in neutral and alkaline environments, thereby promoting reorganization of interfacial water molecules for faster HER kinetics.